HIF-1, Metabolism, and Diabetes in the Embryonic and Adult Heart - Cerychova, Radka; Pavlinkova, Gabriela (Frontiers in Endocrinology, 2018)
The heart is able to metabolize any substrate, depending on its availability, to satisfy its energy requirements. Under normal physiological conditions, about 95% of ATP is produced by oxidative phosphorylation and the rest by glycolysis. Cardiac metabolism undergoes reprograming in response to a variety of physiological and pathophysiological conditions. Hypoxia-inducible factor 1 (HIF-1) mediates the metabolic adaptation to hypoxia and ischemia, including the transition from oxidative to glycolytic metabolism. During embryonic development, HIF-1 protects the embryo from intrauterine hypoxia, its deletion as well as its forced expression are embryonically lethal. A decrease in HIF-1 activity is crucial during perinatal remodeling when the heart switches from anaerobic to aerobic metabolism. In the adult heart, HIF-1 protects against hypoxia, although its deletion in cardiomyocytes affects heart function even under normoxic conditions. Diabetes impairs HIF-1 activation and thus, compromises HIF-1 mediated responses under oxygen-limited conditions. Compromised HIF-1 signaling may contribute to the teratogenicity of maternal diabetes and diabetic cardiomyopathy in adults. In this review, we discuss the function of HIF-1 in the heart throughout development into adulthood, as well as the deregulation of HIF-1 signaling in diabetes and its effects on the embryonic and adult heart.